The Taliban Strategic Model of the Second State Building in Afghanistan - Abdolreza Alishahi; Neda Hasanpuor; Karam Sina (رهیافتهای سیاسی و بین المللی)
In this research, the aim of the authors is answer to this question: "What does the challenges and opportunities Taliban's strategic model in the second state-building in Afghanistan? And what are the challenges and opportunities for the Islamic Republic of Iran? The research method is mixed. The statistical population of this article was the elites and researchers in the fields of political science, regional studies, international relations and geopolitics, who were interviewed in-depth with 40 experts using the theoretical and purposeful sampling method until reaching theoretical saturation. Quantitatively, to evaluate the model, a researcher-made questionnaire with available sampling method was distributed among 90 people from the samples. The data were analyzed in the qualitative part with the qualitative method of database theory and MAXQDA10 software, and in the quantitative part with the method of structural equations, partial least squares algorithm with SMART PLS software. The findings indicated that the strategic model of the Taliban in the second state-building period in Afghanistan has 11 components and 35 indicators as follows: Causal conditions (1. The presence of American and NATO forces, 2. The failure of the state-building process in Afghanistan) Background conditions (3. Emphasis on the realization of an Islamic state 4. Efforts to strengthen the social and popular base) Strategic conditions (5. Efforts to realize a moderate Islamic state 6. Efforts for ethnic unity in Afghanistan 7. Efforts for an alliance with the Republic Islamic Republic of Iran) and intervening conditions (8. International coalition's renewed attack on Afghanistan 9. Intensification of confrontation between Taliban and ISIS), consequences (10. Opportunities of the Islamic Republic of Iran 11. Challenges of the Islamic Republic of Iran)